Social Studies E-Module Containing Balinese Folk Tales Based on Pancasila Student Profiles for Fourth Grade Elementary School Students - Dewi, Ni Made Ari Sintya; Wulandari, I Gusti Agung Ayu (Mimbar Ilmu, 2024)
Social studies lessons that rely solely on textbooks bore students, leading to unmet learning targets in daily tests. Social studies education aims to help students understand themselves, their social environment, and apply this knowledge in daily life.This study aims to produce, determine the level of feasibility, and determine the effectiveness of social studies e-modules containing Balinese folklore based on Pancasila student profiles for grade IV students in elementary schools. The subjects of this study were 1 subject expert, 1 learning design expert, 1 learning media expert, 1 learning language expert, 3 students for individual trials, and 9 students for small group trials. This study is a development research using the Dick and Carey model. Data collection was carried out using observation, interview, questionnaire and multiple choice test methods. The data analysis techniques used were quantitative descriptive analysis, qualitative and inferential statistical analysis (t-test). The results of the study showed a review of learning content experts of 96.87%, a test of learning media experts of 95%, a test of learning design experts of 100%, a test of learning language experts of 97.5%, an individual trial of 98.3% and a small group trial of 97.2%. It can be concluded that there is a significant difference between before and after using the IPS e-module media with innovations containing Balinese folklore based on the Pancasila student profile. The implications of this study are to make students more active in the learning process, understand local wisdom, and form characters in accordance with Pancasila values.